2020
DOI: 10.3390/s20185394
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Methods for the Estimation of Leaf Water and Dry Matter Content: Performances, Potential and Limitations

Abstract: Leaf equivalent water thickness (EWT) and dry matter content (expressed as leaf mass per area (LMA)) are two critical traits for vegetation function monitoring, crop yield estimation, and precise agriculture management. Data-driven methods are widely used for remote sensing of leaf EWT and LMA because of their simplicity, satisfactory accuracy, and computation efficiency, such as the vegetation indices (VI)-based and machine learning (ML)-based methods. However, most of the data-driven methods are utilized at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…When k is large, it can suppress the noise or uncertainty, but may introduce many unrelated learning samples. 44 The accuracies of the KNN methods for different k values were calculated at different deformation characteristics as shown in Fig. 3a.…”
Section: Methodsmentioning
confidence: 99%
“…When k is large, it can suppress the noise or uncertainty, but may introduce many unrelated learning samples. 44 The accuracies of the KNN methods for different k values were calculated at different deformation characteristics as shown in Fig. 3a.…”
Section: Methodsmentioning
confidence: 99%
“…However, it may not be possible to draw an unambiguous conclusion regarding the most appropriate choice of MLRA. For statistical methods, Yang et al [63] compared different MLRAs trained on leaf reflectance only (SVR, PLSR, RFR and K-Nearest Neighbors) for the estimation of EWT and LMA. Overall, their results show that EWT was more accurately estimated with SVR.…”
Section: Estimation Methods Considerations Common To All Four Variablesmentioning
confidence: 99%
“…Moreover, transformations of spectral data could be used in statistical and hybrid methods to extract features or reduce their number for MLRA inputs. Particularly, Yang et al [63] compared statistical methods based on reflectance or spectral indices. They found that estimation accuracy was improved (reduced by 5.7%) when using spectral indices rather than reflectance.…”
Section: Estimation Methods Considerations Common To All Four Variablesmentioning
confidence: 99%